2012
DOI: 10.1530/eje-12-0225
|View full text |Cite
|
Sign up to set email alerts
|

Thyreotropin levels in diabetic patients on metformin treatment

Abstract: Objective: A retrospective study to evaluate the changes in TSH concentrations in diabetic patients treated or not treated with metformin and/or L-thyroxine (L-T 4 ). Methods: Three hundred and ninety three euthyroid diabetic patients were divided into three groups on the basis of metformin and/or L-T 4 treatment: Group (MK/LK), 119 subjects never treated with metformin and L-T 4 ; Group (MC/LK), 203 subjects who started metformin treatment at recruitment; and Group (MC/LC), 71 patients on L-T 4 who started me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 22 publications
7
72
0
2
Order By: Relevance
“…Our findings support the hypothesis that metformin may lead to reductions in TSH levels in patients with treated hypothyroidism, [4][5][6][7]22,23 with no effects in euthyroid patients. 3,6,7 In the former group, we found that metformin monotherapy was associated with a 55% increased risk of low TSH levels (0.4 mIU/L), when compared with sulfonylurea monotherapy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings support the hypothesis that metformin may lead to reductions in TSH levels in patients with treated hypothyroidism, [4][5][6][7]22,23 with no effects in euthyroid patients. 3,6,7 In the former group, we found that metformin monotherapy was associated with a 55% increased risk of low TSH levels (0.4 mIU/L), when compared with sulfonylurea monotherapy.…”
Section: Discussionsupporting
confidence: 88%
“…3,6,7 In the former group, we found that metformin monotherapy was associated with a 55% increased risk of low TSH levels (0.4 mIU/L), when compared with sulfonylurea monotherapy. This finding is concordant with the results of 3 previous studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While three studies in patients with hypothyroidism and/or levothyroxine treatment showed a reduction of serum TSH levels under metformin treatment (9,10,11), a retrospective study demonstrated significantly higher serum TSH levels in euthyroid patients with T2DM treated with metformin compared with those treated with other diabetic agents (12). However, in that study, metformin use was not associated with serum TSH levels after adjustment for several potential confounding factors of which goiter was the only significant one (12).…”
Section: Introductionmentioning
confidence: 79%
“…Za metformin so pokazali, da zniža serumsko raven tirotropina (TSH) (91). Vpliva tudi na prerazporeditev in zmanjšanje maščobnega tkiva v telesu (12).…”
Section: Pleiotropni Učinki Na Druge Organeunclassified